Circulating syncytiotrophoblast-derived extracellular vesicles exhibit variation in release between night and day - Cooke, W; Cerdeira, A; Mejia, C; Kandzija, N; Gill, M; White, K; Thammasate, B; Ri, R; Zhang, W; Redman, C; Vatish, M (Elsevier, 2018)
: Syncytiotrophoblast-derived extracellular vesicles (STBEV) are a key focus of placental research, proposed as a mediator of feto-maternal communication. Recent work has described differences in STBEV number and content in normal and disease states, with attention directed to their value as disease biomarkers in preeclampsia and gestational diabetes. Circadian rhythms are fundamental to human biology; three studies have shown diurnal variation in specific circulating extracellular vesicles outside pregnancy; no study has investigated diurnal variation of STBEV. We hypothesise that STBEV release is different between night and day.